2000
DOI: 10.1007/s004670050040
|View full text |Cite
|
Sign up to set email alerts
|

Management of hemodialysis catheter-related bacteremia - a 10-year experience

Abstract: Between January 1986 and December 1995, 18 episodes of bacteremia occurred in our pediatric patients undergoing chronic hemodialysis on an outpatient basis. Seven episodes were caused by coagulase-negative Staphylococcus, 6 by Staphylococcus aureus, 2 by Mycobacterium, and 1 each by Pseudomonas, Xanthomonas, and Enterococcus. In 6 cases, the catheter was retained with antimicrobial therapy alone, whereas 12 cases required removal of the catheter after some period of time. The subset of cases in which catheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
(31 reference statements)
1
15
1
Order By: Relevance
“…This is in sharp contrast to recent studies (7)(8)(9)11,15) showing that infection is the leading cause for CVC removal in children on long-term HD, with up to 42% of CVCs lost because of infection (Table 1). Our finding of a very low rate of infection-related catheter loss further shows the efficacy of our catheter management protocols.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This is in sharp contrast to recent studies (7)(8)(9)11,15) showing that infection is the leading cause for CVC removal in children on long-term HD, with up to 42% of CVCs lost because of infection (Table 1). Our finding of a very low rate of infection-related catheter loss further shows the efficacy of our catheter management protocols.…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, data on CVC infection rates and survival times in children on HD therapy are scarce. Several studies (4,(7)(8)(9)(10)(11)(12) (Table 1) have reported a rate of bacterial infection in CVCs used for HD in children with ESRD in the range of 1.5 to 4.8 episodes/1000 catheter days. Reported CVC survival times have varied between 84 and 290 days (4,(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of CRBSI in patients in pediatric intensive care units are higher than those in patients in adult intensive care units [8]. Table 1 shows the etiology of CVC-related infections in three studies of children treated with HD [13,15,16]. Coagulase-negative staphylococci and Staphylococcus aureus were the most frequent bacterial isolates, followed by enterococci, gram-negative pathogens, mycobacteria, and Candida spp.…”
Section: Epidemiologymentioning
confidence: 95%
“…Coagulase-negative staphylococci and Staphylococcus aureus were the most frequent bacterial isolates, followed by enterococci, gram-negative pathogens, mycobacteria, and Candida spp. [13,15,16]. Interestingly, Hymes et al [16] reported an outbreak of bacteremia secondary to Enterococcus fecalis in a pediatric hemodialysis unit in which no common source of Enterococcus could be identified by cultures or serotyping.…”
Section: Epidemiologymentioning
confidence: 96%
See 1 more Smart Citation